Pharmacogenetics of carbamazepine - N. A. Shnayder; E. N. Bochanova; D. V. Dmitrenko; R. F. Nasyrova (Эпилепсия и пароксизмальные состояния)
Carbamazepine (CMZ) is a drug from the group of anticonvulsants, similar in chemical structure to tricyclic antidepressants. CMZ is widely used for mental disorders and neurological diseases. The lecture discusses the safety of CMZ in respect to personalized medicine, while considering the pharmacogenetic profile of the patient.The authors declare about the absence of conflict of interest with respect to this publication. All authors contributed equally to this article.